THE CONTRIBUTION OF BANK SYARIAH INDONESIA (BSI) GENTENG IN STRENGTHENING MICRO BUSINESS CAPITAL TO ALLEVIATE POVERTY IN THE SOUTH BANYUWANGI REGION - Alfin farhan Tarhami; Ahmad Nur Izza Wafa; Wiwit Mustafidah (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Poverty in South Banyuwangi is often rooted in limited access to productive capital. This study aims to explore the contribution of Bank Syariah Indonesia (BSI) Genteng in empowering the micro economy to alleviate poverty. Using a descriptive qualitative approach, data was collected through observations and in-depth interviews with BSI management and customers. The results indicate that BSI Genteng plays a strategic role by distributing Sharia People's Business Credit (KUR) financing under an inclusive Murabahah contract for underbanked businesses. This capital strengthening not only increases customers' real income but is also accompanied by spiritual and managerial mentoring that strengthens business resilience. In conclusion, BSI's intervention is effective in breaking dependence on informal financing and encouraging the economic transformation of mustahik (beneficiaries) into self-reliance. This research contribution strengthens the theory of social intermediation and provides practical guidance for Islamic banks in aligning operational standards with local wisdom to achieve the Sustainable Development Goals (SDGs).